Oral health literacy and oral health behavior in pregnant women referring to health centers in south of Kerman province - Marzieh Karimi Afshar; Molook Torabi; Melika Raeisi Afshar; Maryam Deldar (Mashhad University of Medical Sciences, 2020)
Introduction: Low knowledge of oral health in pregnant women can affect both mother and child's health. This study was performed with aim to evaluate oral and dental health literacy and oral health behavior in pregnant women in south cities of Kerman province. Methods: This cross-sectional analytic study was done on 164 pregnant women who referred to health centers in south cities of Kerman province in 2018. Data was collected by demographic characteristic questionnaire (age, education, number of children, number of pregnancy, the economic situation) and the standard questionnaire of oral and dental health literacy )OHL-Q) (including 17 questions in four domains of hearing, comprehension, ability to read and decision -making), assessment of oral health behavior, self-report of oral and teeth health status and DMFT. Data were analyzed by SPSS software (version 21) and Chi-square and ANOVA tests. PResults: In the present study, 63 patients (43.4%) experienced the first pregnancy and most subjects 55 (33.7%) were diploma. 121 women (73.8%) had not dental examination before decision for pregnancy. The most frequent source of oral health information was dentists. Oral health literacy was insufficient in 122 (74.4%). There was significant difference between the level of oral health literacy and educational level(p=0.009),using tooth paste (p=0.005)and tooth brushing (p=0.001). Conclusion: Oral and dental health literacy in pregnant women is inadequate. Dentistry consultation and oral health education before decision for pregnancy are recommended.